2023
DOI: 10.3390/agronomy13061644
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Yield Response and Water Use Efficiency of Cotton under Film-Mulched Drip Irrigation to Magnetized Ionized Water and Bacillus subtilis in Saline Soil in Xinjiang

Abstract: In irrigated agriculture, the combination of multiple regulation measures is an effective method to improve saline soil and promote crop growth. Magnetized ionized water irrigation is considered a promising irrigation water activation technique, while the use of Bacillus subtilis for soil amelioration is environmentally friendly. In this study, magnetized ionized water irrigation and B. subtilis were used to promote cotton growth under film-mulched drip irrigation (FMDI) in saline soil. A two-year field experi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 62 publications
0
2
0
Order By: Relevance
“…25 Other investigations have revealed the significant effects of magnetized-ionized water irrigation on pak choi, eggplants, and cotton. 45,[60][61][62][63] Olant height, stem diameter, leaf number, and crop yield were notably augmented due to this treatment. This study has revealed that magnetized-ionized water irrigation enhanced key parameters including H, LAI, DM, and SPAD during the cotton seedling period.…”
Section: Effects Of Magnetized-ionized Water Irrigation On Crop Growthmentioning
confidence: 95%
“…25 Other investigations have revealed the significant effects of magnetized-ionized water irrigation on pak choi, eggplants, and cotton. 45,[60][61][62][63] Olant height, stem diameter, leaf number, and crop yield were notably augmented due to this treatment. This study has revealed that magnetized-ionized water irrigation enhanced key parameters including H, LAI, DM, and SPAD during the cotton seedling period.…”
Section: Effects Of Magnetized-ionized Water Irrigation On Crop Growthmentioning
confidence: 95%
“…It can enhance seed emergence rates, reduce soil salt content, improve the salt tolerance and stress resistance of crops, increase crop productivity, and enhance the quality of crops and fruits [19,20]. Similarly, the application of ionized technology in irrigation with brackish water has yielded positive outcomes in promoting growth and increasing crop production [14,21]. Ionized water irrigation can improve the growing environment of crops, increase the growth rate and yield of winter wheat, and have a certain buffer effect on soil salt stress [22].…”
Section: Introductionmentioning
confidence: 99%